The Prognostic Nutritional Index May Predict Left Atrial Appendage Thrombus or Dense Spontaneous Echo Contrast in Patients With Atrial Fibrillation - Wang, Zhao; Wang, Binhao; Fu, Guohua; He, Bin; Chu, Huimin; Zhang, Shengmin (Frontiers in Cardiovascular Medicine, 2022)
Objectives The prognostic nutritional index (PNI) is an independent predictor of adverse outcomes in patients with cardiovascular diseases. The presence of left atrial appendage thrombus (LAAT) or spontaneous echo contrast (SEC) is associated with ischemic stroke. The present study aimed to investigate the relationship between the PNI and LAAT/dense SEC in patients with non-valvular atrial fibrillation (AF). Methods In patients with non-valvular AF, we compared demographics, clinical characteristics, and prevalence of LAAT/dense SEC according to the levels of the PNI. The relationship between the PNI and LAAT/dense SEC was observed. Results A total of 406 patients with non-valvular AF were consecutively included from March 2015 to February 2019. Of the study population, 53 patients had LAAT/dense SEC. The percentages of LAAT/dense SEC were 20.4, 14.1, and 4.5% in subjects from the lowest to the highest tertile of the PNI, respectively. Multivariate logistic analysis demonstrated that the PNI was an independent predictor for LAAT/dense SEC (OR 0.89; 95% CI, 0.82–0.97; P = 0.007). Receiver operating characteristic curve analysis revealed that the optimal cutoff value of the PNI for predicting LAAT/dense SEC was 48.0 (area under the curve: 0.68; 95% CI, 0.61–0.75; P < 0.001). The sensitivity and specificity were 83.0 and 47.6%, respectively. The risk of LAAT/dense SEC in patients with a PNI ≤ 48.0 was 2.57-fold higher than that in those with a PNI > 48.0. Conclusion The PNI, calculated based on serum albumin and lymphocyte count, was inversely correlated with LAAT/dense SEC in patients with non-valvular AF. Therefore, it may be considered a predictor for LAAT/dense SEC.